Judicialization of Politics in Indonesian Electoral Law Reform: An Analysis of the Constitutional Court’s Role in Shaping the Direction of Constitutional Policy - Luh Putu Vera Astri Pujayanti (Yayasan Hisnul Muslim Lombok, 2026)
This study aims to analyse the judicialization of politics in Indonesian electoral law reform, with a specific focus on the role of the Constitutional Court in shaping the direction of constitutional policy. The issue is significant because electoral law reform in Indonesia is increasingly determined not only through legislative processes, but also through constitutional adjudication on politically sensitive issues such as electoral thresholds, candidacy requirements, simultaneous elections, ballot design, and electoral disputes. This study uses a qualitative legal research method with a normative-juridical approach. It applies statutory, case, conceptual, and historical approaches by examining the 1945 Constitution of the Republic of Indonesia, electoral laws, Constitutional Court decisions, electoral regulations, and recent scholarly literature on judicialization of politics, electoral justice, constitutional democracy, and separation of powers. The findings show that the Constitutional Court has developed from a constitutional adjudicator into a constitutional policy shaper in electoral reform. Its decisions have influenced the structure of political competition, legislative discretion, electoral fairness, and the institutional direction of democratic governance. Judicialization may strengthen constitutional democracy when it protects political rights and corrects unfair electoral rules. Yet it may also create risks when judicial intervention expands into policy-making, generates legal uncertainty, or weakens democratic deliberation. This study contributes by offering a balanced framework that distinguishes constructive judicialization from problematic judicialization in Indonesian electoral law reform.